2012
DOI: 10.3855/jidc.2340
|View full text |Cite
|
Sign up to set email alerts
|

Detection of carbapenem-resistant Escherichia coli and Klebsiella pneumoniae producing NDM-1 in Lebanon

Abstract: Carbapenem resistance has been encountered globally with poor outcome of infected patients. NDM-1 (New Delhi metallo-beta-lactamase) gene containing organisms have emerged and are now spreading in all continents. This is the first report of Iraqi patients referred to Lebanon from whom carbapenem resistant Enterobacteriaceae were recovered. The genes involved in carbapenem resistance were bla-OXA-48 and the novel NDM-1. This report highlights the alarming introduction of such resistance among Enterobacteriaecae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 24 publications
2
39
0
Order By: Relevance
“…In 2009, a study from Lebanon revealed that 2.5% of E. coli and 7.84% of K. pneumoniae were ESBL producers and carbapenem resistant [antimicrobial brochure at the American University of Beirut Medical Center (AUB-MC)]. Most recently, E. coli and K. pneumoniae with NDM-1 were recovered from Iraqi patients referred for treatment in France [27] and in Lebanon [28]. A summary of the different carbapenemases recovered from patients in Lebanon and its neighboring countries is presented in Table 2.…”
Section: Carbapenemases Producing Enterobacteriaceae Reported From Lementioning
confidence: 98%
See 1 more Smart Citation
“…In 2009, a study from Lebanon revealed that 2.5% of E. coli and 7.84% of K. pneumoniae were ESBL producers and carbapenem resistant [antimicrobial brochure at the American University of Beirut Medical Center (AUB-MC)]. Most recently, E. coli and K. pneumoniae with NDM-1 were recovered from Iraqi patients referred for treatment in France [27] and in Lebanon [28]. A summary of the different carbapenemases recovered from patients in Lebanon and its neighboring countries is presented in Table 2.…”
Section: Carbapenemases Producing Enterobacteriaceae Reported From Lementioning
confidence: 98%
“…As of 2009, NDM-1 had spread from India and Pakistan via medical tourists to the UK, USA, France, Germany, Australia and other countries [26]. In the Gulf region, NDM-1 was first reported in Oman [8], Iraq [27] and, more recently, Kuwait [9] and Lebanon [28]. The bacteria carrying this enzyme are Klebsiella pneumoniae, Escherichia coli, Citrobacter freundii, Enterobacter cloacae, Providencia spp.…”
Section: Classificationmentioning
confidence: 99%
“…The tested isolates showed the lowest resistance to fosfomycin, polymyxin B, colistin and tigecycline (0, 19.6, 26.8, and 33.9%, respectively), but these antibiotics also have limitations and adverse effects (El-Herte et al, 2012). Although Colistin and polymyxin B seem to be the last treatment choice for these isolates; our finding of colistin and polymyxin B resistant MBL-producers is of major concern.…”
Section: Discussionmentioning
confidence: 84%
“…Recent studies conducted in Middle East countries also suggests that this region might be an additional reservoir of NDM producers as it has been reported from Oman [13], Lebanon [14], Saudi Arabia [15,16], and Qatar [17].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular detection of carbapenemase genes using polymerase chain reaction (PCR) based methods was found to be quick, accurate and effective in the detection of specific carbapenemases genes, such as KPC, NDM-1, OXA-48, etc. [13][14][15][16][17]. Simple PCR assays targeting a single carbapenemase type have been used successfully in numerous studies.…”
Section: Introductionmentioning
confidence: 99%